IMPLEMENTASI PENDIDIKAN BERKARAKTER DALAM MENGEMBANGKAN MINAT, SIKAP DAN PERILAKU POSITIF SISWA DISD TERPADU ILMU ALQURAN KAYUAGUNG KABUPATEN OKI TAHUN PELAJARAN 2025/2026 - Wulansari, Ayu (UNISAN JURNAL, 2025)
Character education that is carried out to teach children is to take statements elegantly and to practice in everyday life, so that they can make a positive contribution in the process. There are values of character education given to children such as universality for religion ( Islam), habits, good morals, and then written in the curriculum and activities for children at school. This research took place SD Terpadu Ilmu Al Quran Kayu Agung Regency and discussed the implementation of character education subjects. The research problem is the implementation of character education at SD Terpadu Ilmu Al Quran Kayu Agung This research focuses on: (1) How to implement character education about wanting to be happy, behavior, and positive outcomes for students at SD Terpadu Ilmu Al Quran Kayu Agung Regency (2) What about the problem of implementing character education at SD Terpadu Ilmu Al Quran Kayu Agung Regency(3) and what are the supporting factors and constitution of the implementation of this character education. This study aims to describe the implementation of character education at SD Terpadu Ilmu Al Quran Kayu Agung. This study uses a qualitative approach with a descriptive method. Therefore, this research is a qualitative descriptive study. Research data were collected through observation, interviews, and documentaries. And for data that looks bright, categorization is made using a coding system. Data validity is done through triangulation method. The data were analyzed during and after the study. The results showed that the implementation of character education in SD Terpadu Ilmu Al Quran Kayu Agung Regency had main competencies that were mastered by each teacher, namely; RPP regulates competence, curriculum implementation and evaluation. So, the implementation of character education for each lesson is through: making graduate competency standards (SKL) which are prepared by standards (SK) and setting up learning directors, learning evaluation strategies apply all of these improvements with supporting factors and limiting factors. It has a big meaning, it has research implications that every teacher must have professionalism, good workers, fresh functions, and credible performance. That is, having the implementation of character education is education with aspects of building moral, (ethical-aesthetic), cognitive, feeling, and psychomotor axioms